Prophylactic Effectiveness of Phenylephrine 100 mcg and Ephedrine 10 mg on the Incidence of Spinal Anesthesia Induced Hypotension in Patients Undergoing Cesarean Section - Etania, Cassandra; Hanafie, Achsanuddin; Lubis, Andriamuri Primaputra (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Birth by cesarean section (C-section) has increased significantly, with a high risk of maternal hypotension due to spinal anesthesia. Objective: This study aims to compare the prophylactic effectiveness of phenylephrine 100 mcg and ephedrine 10 mg in preventing spinal anaesthesia induced hypotension in C-section patients. With a focus on safety and reducing the incidence of fetal acidosis, the results of the study are expected to provide clinical insights that can improve the safety and quality of care for pregnant women undergoing this procedure. Methods: This study compared the effectiveness of phenylephrine 100 mcg and ephedrine 10 mg in preventing hypotension due to spinal anesthesia in cesarean section patients in four hospitals in Medan, Indonesia. Using a double-blind design, 40 patients aged 18-40 years were randomly selected, and blood pressure and heart rate were measured before and after anesthesia. Data were analyzed using SPSS, and ethical aspects were taken care of through informed consent. Results: This study found that phenylephrine 100 mcg was more effective than ephedrine 10 mg in preventing spinal anaesthesia induced hypotension in cesarean section, with more stable blood pressure and mean arterial pressure (MAP) at the 5th, 10th, and 15th minutes (p-value < 0.05). Although ephedrine remained above 100 mmHg for systolic blood pressure (SBP), the incidence of nausea and vomiting was slightly higher in the ephedrine group. Results support phenylephrine as the primary choice for hypotensive management. Conclusion: Phenylephrine 100 mcg is more effective than ephedrine 10 mg in preventing hypotension due to spinal anesthesia, without increasing heart rate. Despite causing nausea, ephedrine has a higher incidence of vomiting. Ephedrine is recommended if phenylephrine is not available, with further studies needed for lower doses of phenylephrine.